Nephritic syndrome and acute kidney injury following poststreptococcal glomerulonephritis in pediatric patients: A case report - Indriastuti, Endah; Rangkuti, Rahmah Yasinta; Kurniawan, Alvin Hartanto (Svāsthya: Trends in General Medicine and Public Health, 2024)
Acute kidney injury (AKI) is characterized by an abrupt decrease in glomerular filtration rate, manifesting as an increase in serum creatinine or oliguria. Nephritic syndrome, a manifestation of glomerulonephritis, presents with hematuria, hypertension, decreased urine output, and edema. This case report discusses an 11-year-old Asian boy who presented with decreased urination, shortness of breath, hypertension, and bilateral leg edema. Urinalysis revealed hematuria, proteinuria, and dysmorphic erythrocytes, while serum creatinine was elevated with a decreased estimated glomerular filtration rate (eGFR). The patient had a positive ASTO test, indicating poststreptococcal glomerulonephritis as the underlying cause of nephritic syndrome and AKI. Although most cases of poststreptococcal glomerulonephritis in children have a favorable outcome, some cases can develop into a serious, life-threatening condition that requires careful attention. This case highlights the importance of early detection and management of poststreptococcal glomerulonephritis to prevent progression to nephritic syndrome and AKI, especially in resource-limited settings. Modest examination modalities can facilitate early detection and faster patient management, particularly in developing countries, to reduce the risk of mortality associated with severe AKI in pediatric patients.